A Discrete Nonlinear Tracking-Differentiator and Its Application in Vibration Suppression of Maglev System. (19th June 2020) - Wang, Zhiqiang; Long, Zhiqiang; Xie, Yunde; Ding, Jingfang; Luo, Jie; Li, Xiaolong
Abstract : Vibration of the maglev train levitation system is harmful to riding comfort and safety. The signal processing method is effective in vibration control. In this paper, a novel kind of second-order nonlinear tracking differentiator is proposed and applied to suppress the vibration phenomenon. The switching curves of the second-order discrete time optimal control system are presented by the isochronous region method. A synthetic function is acquired depending on the cases whether a point in the phase plane can reach the switching curves within one sample step. The discrete form of tracking differentiator is constructed based on the position relationship between the state point and the characteristic curves. Numerical simulation shows that this discrete tracking differentiator can quickly track an input signal without overshoot and chattering and can produce a good differential signal. A test in a maglev test bench also demonstrates the effectiveness of the tracking differentiator in the suppression of the track-train vibration.